Distribution and length-weight relationships of Hilsa shad Tenualosa ilisha in the Bilah River, Labuhanbatu Regency, North Sumatera Province, Indonesia - Rusdi Machrizal; Khairul Khairul; Juliana Nasution; Rivo H. Dimenta; Arman Harahap (Aceh Journal of Animal Science, 2019)
Hilsa shad Tenualosa ilishais of the indigenous fish species and the icon of the Labuhanbatu Regency, Indonesia. Presently, a very limited study was done in this species. Hence, the purpose of this study was to analyse the distribution and growth patterns based on the length-weight relationship of Hilsa shad T. ilishaon Bilah River, Labuhanbatu District, Sumatera Utara Province, Indonesia. Sampling was carried out for 3 months starting in February-April 2019 with the exploration method. Determination of sampling locations based on information from local fishermen. Analysis of distribution data used the Morisita index and growth patterns used the Linear Allometric Model (LAM). The analysis results of Hilsa shad distribution indicated that these fish were distributed in groups/clustered with the Morisita index value of 2.211-2.314. The growth pattern of the fish was negative allometric with a value of b3. Correlation analysis showed that DO was closely related to distribution (r2=0.661), meanwhile, light penetration was closely related to growth patterns (r2=0.914). It is concluded that the distribution of Hilsa shad fish in the Bilah River was in groups or clustered, with a negative allometric growth pattern. Keywords: Hilsa Shad, distribution, growth pattern, Tenualosa ilisha